Stem cells research: therapeutic potentials and ethical issues from Islamic perspective - Che Mohamad, Che Anuar; Hashi, Abdurezak Abdulahi (IIUM Press, International Islamic University Malaysia, 2018)
The advancement in human stem cell research has promised a viable alternative treatment for a range of ‘incurable diseases’ such as neurological diseases. To date, several studies have documented substantial evidences on the therapeutic properties of stem cells in promoting repair in different diseases including common neurological disorders i.e. ischaemic stroke and spinal cord injury. However, the progress of stem cell research has been surrounded by ethical issues which largely due to the usage of human embryos as one of the sources. These embryonic stem cells which originally derived from human embryo of aborted foetus or already existing human embryonic stem cells (hESCs) lines, has sparked an intense moral and religious argument among people of various faith, including Muslim community. From the therapeutic point of view, amongst the currently available stem cells, hESCs show the greatest potential for the broadest range of cell replacement therapies and are regarded as the most commercially viable. This review focuses on the major ethical issues, particularly to Muslim community, related to human embryonic stem cells research with special emphasis on the moral status of the embryo and the beginning of life according to the Islamic ethics and rulings. In this paper, we also discuss some ethical positions towards embryonic stem cell research in the Islamic world, including official regulations existing in some Muslim countries. We examine the justification and the necessity on the usage of hESCs following the newly discovered Induced Pluripotent Stem Cells (IPSCs) in the laboratory. In addition, we supplement the discussions with the general views and positions from the other two Abrahamic religions i.e. Christianity and Judaism.